Visual GUI Testing of Embedded Systems - Makarewicz, Maciej (My University, 2016)
The increasing demand on software quality drives emergence of new testing technologies. While well-known methods exist for automated graphical user interface (GUI) testing, such as coordinate-based, widget-based and visual GUI testing (VGT), not much has been done to automate GUI testing of software for embedded systems. This thesis approaches this problem by evaluating the applicability of VGT – a technology that analyses the bitmap contents of the system-under-test’s (SUT) GUI to automatically drive tests. The study was conducted in cooperation with a Gothenburg-based company that operates in the automotive ﬁeld. A prestudy was conducted in order to recognise the company’s needs when it comes to VGT of their embedded systems. A VGT framework was implemented. Furthermore, an open-source GUI automation tool was adapted to match the company’s needs. Finally, experiments were conducted that compared the performance of the two resulting VGT frameworks when it comes to test-case (TC) development and TC maintenance costs. The work concludes with guidelines on how to apply VGT for testing of software for embedded systems, with emphasis on how to minimise TC development and maintenance costs.
Keywords: Data- och informationsvetenskap; Computer and Information Science